Partisipasi Siswa dalam Quantum Wiriting: Sebuah Studi Pembelajaran Menulis pada Siswa Kelas XII SMAN di Kabupaten Sekadau - Kusnadi Kusnadi (Journal of Edukasi Borneo, 2021)
The purpose of this study was to describe an increase in the ability to write job application letters through the Quantum Writing method in Class XII SMAN students in Jongkong. This type of research was classroom action research. The subjects in this study amounted to 35 people which were carried out in 2 cycles. Data collection techniques consisted of observation and tests. The procedures used were (1) planning, (2) implementation, (3) observation, (4) reflection. The results of this study indicated it can improve learning activities. This can be seen from the teacher's activities in the first cycle obtained an average of 27.5 with "enough" criteria and increased in the second cycle with an average of 34 with "good" criteria. In the student activity in the first cycle obtained an average of 29 with "enough" criteria and increased in the second cycle with an average score of 32 with "good" criteria. The results of the classical learning completeness analysis in the first cycle were 50% with an average value of 72.9. In the second cycle, the classical learning completeness was 75% with an average value of 79.6. Based on these data, classical learning completeness has increased. Thus, it can be concluded that the application of the Quantum Writing method can improve learning activities in learning to write student job applications in class XII.   ABSTRAK Tujuan penelitian ini untuk mengetahui gambaran peningkatan kemampuan menulis surat lamaran pekerjaan melalui metode Quantum Writing pada siswa Kelas XII  SMAN  di Jongkong. Jenis penelitian ini adalah penelitian tindakan kelas.Subjek dalam penelitian ini berjumlah 35 orang yang dilaksanakan dalam 2 siklus.Teknik pengumpulan data terdiri dari observasi dan tes.Prosedur yang digunakan adalah (1) tahap perencanaan, (2) pelaksanaan, (3) observasi, (4) refleksi.Hasil penelitian ini menunjukkan dapat meningkatkan aktivitas belajar. Hal ini dapat dilihat dari aktivitas guru pada siklus I diperoleh rata-rata 27,5 dengan kriteria “cukup” dan meningkat pada siklus II dengan rata-rata 34 dengan kriteria “baik”. Pada aktivitas siswa pada siklus I diperoleh rata-rata 29 dengan kriteria “cukup” dan meningkat pada siklus II dengan skor rata-rata 32 dengan kriteria “baik”. Hasil analisis ketuntasan belajar secara klasikal pada siklus I sebesar 50% dengan nilai rata-rata 72,9. Pada siklus II ketuntasan belajar secara klasikal sebesar 75% dengan nilai rata-rata 79,6. Berdasarkan data tersebut ketuntasan belajar klasikal mengalami peningkatan.Dengan demikian dapat disimpulkan bahwa penerapan metode Quantum Writing dapat meningkatkan aktivitas belajar dalam pembelajaran menulis surat lamaran pekerjaan siswa di kelas XII . KATA KUNCI: menulis, hasil belajar, quantum writing